Knowledge Regarding Needle Stick Injury among Nurses in Tertiary Care Hospital Jhapa Nepal - Adhikari, Ganga; Yadav, Kiran Kumari (Medical Journal of Eastern Nepal, 2022)
Background Needle Stick Injury (NSI) is the wound or cut caused by the needles that unintentionally tear/puncture the skin that may result in exposure to contaminated blood and the body fluids. Nursing workers are on high risk of exposure of blood borne germs i.e. HIV, HBV and HCV. According to WHO study, the annual estimated proportions of health- care workers (HCW) exposed to blood-borne pathogens globally were 2.6% for HCV, 5.9% for HBV, and 0.5% for HIV, corresponding to about 16,000 HCV infections and 66,000 HBV infections in HCW worldwide. Methods The quantitative research for approach was adopted for this study and descriptive survey research design was selected for this study. A study to assess knowledge regarding needle stick injury among nurses in tertiary care Hospital, Jhapa Nepal was conducted among the nurses from 13 th March 2022 to 20 th March 2022. Hundred nurses were selected by using convenient sampling. SPSS Version 20 was used for data analysis. Results The collected data was analyzed by using descriptive and inferential statistics. This study result showed that 73% had average knowledge, 7% had good knowledge and 20% had poor knowledge respectively. Chi–square value revealed that there was significant association between knowledge with demographic variables of educational qualification and working experiences, where p value was less than 0.05 (p<0.05). Conclusion This study concluded that the majority of nurses having average knowledge. They need to improve their knowledge.